EPIDEMIOLOGICAL PROFILE AND FETO-MATERNAL OUTCOME OF TWIN PREGNANCY: A PROSPECTIVE OBSERVATIONAL STUDY - Islam, Ansa; Iram Sarwar,; Azmat Ali Shah,; Mujahid ul Islam,; Humaira JAdoon,; Attiya Bibi, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Twin pregnancies are complex and have often been associated with various complications affecting both mother and baby. Understanding the different maternal and foetal outcomes can provide crucial insights for healthcare practitioners. The aim was to determine the maternal and foetal outcomes of twin pregnancies and understand the factors influencing these outcomes. Methods: A prospective observational study was conducted with women experiencing twin pregnancies of more than 28 weeks gestation. Patients were followed up until 7 days postnatally and the outcomes were analyzed against various parameters such as age, foetal presentation, and mode of delivery. Statistical software SPSS V 26 was utilized for data analysis and ethical considerations were duly met. Results: A total of 22,922 deliveries were recorded, with 195 being twin pregnancies. Most twin deliveries were among women aged 20-29 years, with nearly half being first pregnancies. Major findings include a prevalence of preterm deliveries (59.6%), a high incidence of maternal anaemia (54%), and a significant number of neonatal intensive care unit (NICU) admissions (45.45%). No statistically significant difference was observed in the feto-maternal outcomes about the mode of delivery or booking status. Conclusion: Twin pregnancies are associated with a higher likelihood of preterm deliveries, maternal anaemia, and newborn NICU admissions. Importantly, the mode of delivery and booking status did not significantly affect the feto-maternal outcomes. This study underscores the need for individualized patient care in managing twin pregnancies.